Формативті бағалаудың оқушы ынтасын жоғарылатуға ықпалы - Трусбаева, Е.С. (My University, 2016)
Formative assessment not only increases the motivation to learn, but also the skills of independent work of students. The paper also shows the effectiveness of formative assessment in learning the Kazakh language and its role in shaping a sense of student success.
Keywords: proficiency courses; formative assessment; student self-improvement